Epidemiology kept simple an introduction to traditional and modern epidemiology - Gerstman, B. Burt (Wiley-Blackwell, 2013)
This text introduces the history and the use of epidemiology as a discipline. It clearly explains the concepts and techniques associated with traditional epidemiology, the design of trials and the analysis of observational data and advanced biostatistical and epidemiologic techniques. It includes practical exercises, case studies and real-world applications throughout and explains all new terminology with minimum use of technical language.